Problems of learning and teaching modern Arabic/ Musykilah Ta’lîmi al-Lugha al-Arabiyah al-Hadîtsah wa Ta’lîmiha - Firdaus, Dadang (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
AbstractTeaching Arabic is a form of classical teaching that is still ongoing from generation to generation to this day. In addition , the learning process applied is of course very varied . The curriculum provided, the methods applied and the approaches and techniques implemented have undergone many changes. Thus, of course, it is hoped that an escalation in its application along with the times and the increasing need for the use of modern facilities, this is in line with the rapid rate of utilization of media or learning facilities in all branches of science. Therefore, it is hoped that learning Arabic certainly does not lose its involvement in modern learning models. The use of technology-based learning media today is highly encouraged in Arabic learning, the use of media in an approach turns out to have a very large influence in stimulating the interest and attention of students, while the media in question includes various forms, including internet-based learning media, television-based learning media, audio-based learning media and others, so that learners no longer feel Arabic as